1989
DOI: 10.1111/j.1600-0773.1989.tb00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Methyl Mercury Binding Sites on Tubulin Subunits and Microtubules

Abstract: We have studied the localization and affinity of methyl mercury hydroxide (MeHg) binding sites on microtubules. There is one class of binding sites for MeHg on tubulin, a high affinity class with fifteen sites. MeHg binds to tubulin stoichiometrically within microtubules, and does not induce microtubule disassembly at this low binding ratio. MeHg binds in microtubules either in the presence or absence of free tubulin subunits but free subunits act as uncompetitive inhibitors for MeHg binding to the polymer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…In this way, any disturbance of these dynamic structures or their polymerization/depolymerization status could compromise cell survival [133, 134]. MeHg has long been known to be a potent inhibitor of microtubule polymerization [135137]. In vitro studies demonstrated that MeHg has high affinity for tubulin sulphydryl groups (-SH), depolymerizing cerebral microtubules, and directly inhibiting their assembly [135, 137].…”
Section: Mechanisms Of Mehg-induced Developmental Neurotoxicitymentioning
confidence: 99%
“…In this way, any disturbance of these dynamic structures or their polymerization/depolymerization status could compromise cell survival [133, 134]. MeHg has long been known to be a potent inhibitor of microtubule polymerization [135137]. In vitro studies demonstrated that MeHg has high affinity for tubulin sulphydryl groups (-SH), depolymerizing cerebral microtubules, and directly inhibiting their assembly [135, 137].…”
Section: Mechanisms Of Mehg-induced Developmental Neurotoxicitymentioning
confidence: 99%
“…Mercury compounds are known to interact with tubulin and to affect tubulin assembly (Vogel et al 1989;Duhr et al 1993;Liliom et al 2000). Hence, in previous publications (Thier et al 2003;Stoiber et al 2004) we have advanced the theory that the chromosomal genotoxicity of mercury may result, at least in part, from interaction(s) with cytoskeletal proteins.…”
Section: Introductionmentioning
confidence: 95%
“…MeHg has long been known to be a potent inhibitor of microtubule polymerization, and this effect is presumably caused by the S-mercuration of the microtubules by MeHg (Abe et al, 1975;Sager et al, 1983;Vogel et al, 1985Vogel et al, , 1989. Vogel et al (1989) found that there is a class of binding sites that have high affinities for MeHg on tubulin and that MeHg binds to tubulin stoichiometrically within microtubules. Tubulin has been found to contain thiols with low pKa values (Britto et al, 2002).…”
Section: The Disruption Of Microtubules and S-mercurationmentioning
confidence: 99%